Disentangling transport movement patterns of trucks either transporting pigs or while empty within a swine production system before and during the COVID-19 epidemic - Picasso-Risso, Catalina; Vilalta, Carles; Sanhueza, Juan Manuel; Kikuti, Mariana; Schwartz, Mark; Corzo, Cesar A. (Frontiers in Veterinary Science, 2023)
Transport of pigs between sites occurs frequently as part of genetic improvement and age segregation. However, lack of transport biosecurity can have catastrophic implications if not managed properly as disease spread would be imminent. Still, there is a lack of a comprehensive study of vehicle movement trends within swine systems in the Midwest. Here, we aimed to describe and characterize vehicle movement patterns within one large Midwest swine system representative of modern pig production to understand movement trends, proxies for biosecurity compliance, and identify potential risky behaviors that can result in a higher risk for infectious disease spread. Geolocation tracking devices recorded vehicle movements of a subset of trucks and trailers from a production system every five minutes, and every time tracks entered a landmark between January 2019 and December 2020, before and during the COVID-19 pandemic. We described 6213 transport records from twelve vehicles controlled by the company. One-hundred-and-fourteen predefined landmarks were included during the study period, representing five categories of farms and truck-wash facilities. Results showed that trucks completed the majority (76.4%, 2111/2762) of the recorded movements. The seasonal distribution of in-coming movements was similar across years (P-value >0.05), while during the 2019 winter and summer seasons showed the highest in-coming movements to sow farms than any other season, year or production type (P-value <0.05). More than half of the in-movements recorded occurred within the triad sow farms, wean-to-market, and truck-wash facilities. Overall, time spent at each landmark was 9.08% higher in 2020 than 2019, without seasonal highlights, but with notable higher time spent at truck wash facilities than any other type of landmark. Network analyses showed high connectivity among farms with identifiable clusters in the network. Furthermore, we observed a decrease in connectivity in 2020 compared to 2019, as indicated by the majority of network parameter values. Further network analysis will be needed to understand its impact on disease spread and control. Still, the description and quantification of movement trends reported in this study, provides findings that might be the basis for targeting infectious disease surveillance and control.